Nutrimental and sensorial caracterization of muicle and amaranth beverage - Cruz Hernández, Javier (2019)
The muicle (Justicia spicigera S.) is rich in phenolic compounds and is apreciated by his hypogleusemic effect, it mixed with protein and amaranth fiber (Amaranthus hipochondriacus L.) and with the antioxidants of the pulp of berries fruits can be made beverages with hight aceptance and nutritional value. Scarce studies have been carried out with extract of muicle for the made of functional beverages, so the objetive was to perform nutritional and sensorial characterization of two beverages, one made with whey (Beb1) and another with amaranth flour (Beb2) like protein sources, both mixed with muicle and berries fruit (Fragaria x Ananassa Douch. and Rubus spp). Sensory characteristics were evaluated with 50 volunteers and protein, fiber, fat, sodium, total solids, °Bx, pH, and titratable acidity were quantified in both beverages. The Beb2 received the highest acceptance with the sensory test and resulted with a total solids content (76 mg.L-1), titratable acidity (38.4%) and pH (5.2); besides a protein (9.25%) and fiber (16.67%) content acceptable. The fiber content of Beb1 was (14.5%) and protein (6.35%), with a caloric content of 44.1 kcal per 365 mL portion, while Beb2 was 40.2 kcal. Both beverages were in inocuos parameters established in mexican official norms. The Beb2 had the best nutritional characteristics, a lower caloric level and better acceptance than Beb1